2021
DOI: 10.3390/nu13113886
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Feeding Improves Tolerance of Parenteral Nutrition in Preterm Newborns

Abstract: (1) Background: The tolerance of preterm newborns for the high nutritional intakes given by parenteral nutrition (PN) is still debated because of the risk of metabolic complications. Despite enteral nutrition (EN) being the preferred route of nutrition, an exclusive enteral feeding is not always possible, as in preterm newborns, the gut is immature and less tolerant of EN. We aimed to study the impact of a minimal enteral feeding (MEF) on the possible early metabolic complications of PN in a cohort of preterms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…More evidence is emerging regarding the advantages of enteral nutrients over parenteral [21] and well-known benefits of enteral feeding and breastmilk on cerebral growth, brain structures, and neurodevelopment [23,47]. Moreover, the study by Boscarino et al found that early enteral feeding may improve tolerance of parenteral nutrition in preterm newborns and may prevent PN related metabolic complications, such as hyperglycemia, hypertriglyceridemia, and metabolic acidosis [25]. Early feeding with own mother's milk is now a preferred practice for very preterm infants.…”
Section: Early Nutrient Intake and Neurodevelopmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More evidence is emerging regarding the advantages of enteral nutrients over parenteral [21] and well-known benefits of enteral feeding and breastmilk on cerebral growth, brain structures, and neurodevelopment [23,47]. Moreover, the study by Boscarino et al found that early enteral feeding may improve tolerance of parenteral nutrition in preterm newborns and may prevent PN related metabolic complications, such as hyperglycemia, hypertriglyceridemia, and metabolic acidosis [25]. Early feeding with own mother's milk is now a preferred practice for very preterm infants.…”
Section: Early Nutrient Intake and Neurodevelopmentmentioning
confidence: 99%
“…More evidence suggests that early enteral nutrient and energy intake is associated with better cerebral growth, head growth, brain structure, and neurodevelopment [21,23,24]. Moreover, early enteral feeding may improve tolerance of PN [25], reducing adverse metabolic effects, such as hyperglycemia, which also may be related to neurodevelopmental impairment [26]. Thus, current nutritional strategies recommend early enteral feeding with human milk (HM) and enhanced nutrient provision with HM fortification [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are well established nutritional recommendations from various expert groups pertaining to macro- and micronutrient requirements of preterm infants [ 4 , 16 ], the recommendations do not account for an individual preterm infant’s ability to assimilate nutrients or the ability to overcome potential aberrance in metabolic pathways [ 5 , 9 , 17 ]. As an example, some preterm infants, (especially those around the threshold of viability) experience metabolic immaturity and instability leading to sustained periods of hyperglycaemia and hypertriglyceridemia, meaning that some nutritional goals are not met during a time of rapid growth and organ development [ 9 , 17 ]. Current strategies to manage metabolic complications include the use of insulin (which is not without risk), or potentially an even cruder strategy of reducing the amount substrate (e.g., glucose and lipid) delivered with associated negative sequalae on macro- and micronutrient intake [ 9 , 10 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, some preterm infants, (especially those around the threshold of viability) experience metabolic immaturity and instability leading to sustained periods of hyperglycaemia and hypertriglyceridemia, meaning that some nutritional goals are not met during a time of rapid growth and organ development [ 9 , 17 ]. Current strategies to manage metabolic complications include the use of insulin (which is not without risk), or potentially an even cruder strategy of reducing the amount substrate (e.g., glucose and lipid) delivered with associated negative sequalae on macro- and micronutrient intake [ 9 , 10 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal anastomosis(IA) is a frequently used surgical procedure in pediatric surgery,however, no de ned initial oral feeding time was suggested to date [1,2].Traditionally,a 4-5 days of fasting or traditional oral feeding(TOF) would be chosen by pediatric surgeon to avoid dehiscence of anastomosis after intestinal anastomosis [3][4][5].Many opposite effects caused by long fasting were proven,such as atrophy of the villi, decreased activity of disaccharidase, reduction of intestinal mucosa, and intestinal microbiota dysbiosis [2,6]. In contrast,early oral feeding(EOF) could be bene cial in gut development, regeneration of the intestinal mucosal epithelium, maintenance of the integrity of the gut barrier, and prevention of bacterial translocation [7,8].…”
Section: Introductionmentioning
confidence: 99%